2010
DOI: 10.1016/j.ijmecsci.2009.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Impact behaviour of hollow sphere agglomerates with density gradient

Abstract: Abstract. This paper presents a study on the influence of the density gradient profile on the mechanical response of graded polymeric hollow sphere agglomerates under impact loading.Quasi-static, standard split Hopkinson pressure bar (SHPB) tests as well as higher speed direct impact Hopkinson bar tests and Taylor tests are performed on such hollow sphere agglomerates with various density gradient profiles. It is found that the density gradient profile has a rather limited effect on the energy absorption capac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(35 citation statements)
references
References 21 publications
1
34
0
Order By: Relevance
“…Examples are the advanced pore morphology (AMR) concepts (Stobener et al, 2008;Lehmhus et al, 2010) where spherical aluminium foam elements are bonded together, or syntactic foams comprising hollow spheres embedded into a homogeneous polymeric or metallic matrix (Sanders and Gibson, 2003;Zeng et al, 2010).…”
Section: Experimental and Numerical Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Examples are the advanced pore morphology (AMR) concepts (Stobener et al, 2008;Lehmhus et al, 2010) where spherical aluminium foam elements are bonded together, or syntactic foams comprising hollow spheres embedded into a homogeneous polymeric or metallic matrix (Sanders and Gibson, 2003;Zeng et al, 2010).…”
Section: Experimental and Numerical Studiesmentioning
confidence: 99%
“…Experimental studies were performed under quasi-static loading, standard Split Hopkinson Pressure Bar test (21 m/s) as well as direct impact loading (41 m/s) on sphere agglomerates with graded density by Zeng et al (2010). The later study corroborated the numerical findings in Anlas et al (2000) that placing the strongest layer as the first impacted layer and weakest layer as the last had some benefit in terms of maximum energy absorption with a minimum force level transmitted to the protected structures.…”
Section: Experimental and Numerical Studiesmentioning
confidence: 99%
“…Zeng et al. [23] performed a series of experiments to test the dynamic responses of hollow sphere metal foams with density gradients. It turned out that a winning strategy in term of more absorbed energy with a low transmitted force could consist of placing the "hardest" layer as the first impacted layer and the "weakest" layer in contact with the protected structure to reduce the transmitted force.…”
Section: A N U S C R I P Tmentioning
confidence: 99%
“…Clearly, there are some disagreements in the aforementioned findings [23,24,25,28,29,31], and limited detailed analysis focuses on the dynamic response of the graded Voronoi structures. Therefore, it is much necessary to further investigate this comprehensively and systematically.…”
Section: A N U S C R I P Tmentioning
confidence: 99%
“…Their results showed that the plateau stress of the density-graded foam was higher than the uniform one. Zeng et al [19] investigated the influence of the density gradient on the mechanical response of graded polymeric hollow sphere agglomerates under impact loading. In the early stage, the force at the distal end was found much higher when the strongest layers were placed near the proximal end.…”
Section: Introductionmentioning
confidence: 99%